Tourism Sector Competitiveness in Portugal: applying Porter's Diamond - Cristina Estevão; Sara Nunes; João Ferreira; Cristina Fernandes (Tourism & Management Studies)
The tourism sector has stood out for its enormous capacity for growth on a global scale and holding a relevant role both as a tool for the competitiveness and as a driver of regional development. This profile stems not only from its multiplier effects but also the opportunities susceptible to identification within the scope of offsetting regional disparities in growth and prosperity. The objective of this research consists of evaluating the competitiveness of the regional areas and directorates of tourism in Portugal. We have used primary data (a sample of 446 companies), through a questionnaire aimed at companies displaying the activities characteristic of the World Tourism Organisation satellite account. Through the application of Porter’s Diamond Model, we attained at a conceptual model through recourse to the Partial Least Square – Path Modelling technique with the objective of analysing the relationships unfolding among the determinant variables to competitiveness in the tourism sector. Despite the results returned proving clear, we also verify that encapsulating competitiveness proves no easy task given how Portugal reports regions with simultaneously very varied and very specific characteristics